Does heterotopic ossification affect the outcomes of cervical total disc replacement? A meta-analysis - Zhou, Hao-han; Qu, Yang; Dong, Rong-peng; Kang, Ming-yang; Zhao, Jian-wu (Spine (Philadelphia, Pa. 1976), 2015)
Meta-analysis. The purpose of this study was to answer the following questions: (1) Does heterotopic ossification (HO) negatively influence clinical outcomes after cervical total disc replacement (CTDR)? (2) Should patients be classified into HO and non-HO groups? (3) Is there a more rational classification? Heterotopic ossification has emerged as a common complication after CTDR and has been an important reason for reoperation, thus limiting the use of the surgery. However, the influence of HO on clinical outcomes after CTDR has not been well established. A meta-analysis was conducted with studies identified by searches of MEDLINE, EMBASE, and the Cochrane Library. We calculated the weighted mean differences of the visual analogue scale pain score, Neck Disability Index, and range of motion (ROM). Patients were classified into 2 groups under 3 classifications on the basis of the grade of HO. Results were pooled using a fixed effect model or a random effects model, according to the heterogeneity. There were significant differences in ROM under all 3 classifications. The visual analogue scale pain score and the Neck Disability Index between the patients with and without HO showed no significant difference after CTDR. Significant differences in visual analogue scale pain score were observed when patients were classified into a "high-grade HO" group (McAfee grades 3 or 4 HO) and a "low-grade HO" group (McAfee grade 0, 1, or 2 HO). The presence of HO is not associated with clinical outcomes after CTDR. However, the severity of HO actually impacts clinical outcomes in an inverse manner, which needs further investigation. It is inappropriate to classify patients on the basis of the presence of HO; further studies of the classifications (ROM-affecting HO vs. ROM-preserving HO; high-grade HO vs. low-grade HO) and cervical stability after CTDR are needed. 2.